An interdisciplinary research perspective on the future of multi-vector energy networks. (February 2022) - Taylor, P.C.; Abeysekera, M.; Bian, Y.; Ćetenović, D.; Deakin, M.; Ehsan, A.; Levi, V.; Li, F.; Oduro, R.; Preece, R.; Taylor, P.G.; Terzija, V.; et al.
Highlights: Most important aspects for designing, planning and operating MVENs are addressed. Architectures and interdependencies of energy network infrastructures are reviewed. Implementation of novel technologies, concepts and algorithms are discussed. The role of policy, markets and regulation in facilitating MVENs is reported. The aspects of risks and uncertainties in operation of future MVENs are elaborated. Abstract: Understanding the future of multi-vector energy networks in the context of the transition to net zero and the energy trilemma (energy security, environmental impact and social cost) requires novel interdisciplinary approaches. A variety of challenges regarding systems, plant, physical infrastructure, sources and nature of uncertainties, technological in general and more specifically Information and Communication Technologies requirements, cyber security, big data analytics, innovative business models and markets, policy and societal changes, are critically important to ensure enhanced flexibility and higher resilience, as well as reduced costs of an integrated energy system. Integration of individual energy networks into multi-vector entities opens a number of opportunities, but also presents a number of challenges requiring interdisciplinary perspectives and solutions. Considering drivers like societal evolution, climate change and technology advances, this paper describes the most important aspects which have to be taken into account when designing, planning and operating future multi-vector energy networks. For this purpose, the issues addressing future architecture, infrastructure, interdependencies and interactions of energy network infrastructures are elaborated through a novel interdisciplinary perspective. Aspects related to optimal operation of multi-vector energy networks, implementation of novel technologies, jointly with new concepts and algorithms, are extensively discussed. The role of policy, markets and regulation in facilitating multi-vector energy networks is also reported. Last but not least, the aspects of risks and uncertainties, relevant for secure and optimal operation of future multi-vector energy networks are discussed.